Scoping review of pediatric tonsillectomy quality of life assessment instruments. (8th March 2017) - Kao, Stephen Shih‐Teng; Peters, Micah D. J.; Dharmawardana, Nuwan; Stew, Benjamin; Ooi, Eng Hooi
Abstract : Objectives/Hypothesis: Sleep‐disordered breathing or recurrent tonsillitis have detrimental effects on the child's physical health and quality of life. Tonsillectomy is commonly performed to treat these common conditions and improve the child's quality of life. This scoping review aims to present a comprehensive and descriptive analysis of quality of life questionnaires as a resource for clinicians and researchers when deciding which tool to use when assessing the quality of life effects after tonsillectomy. Study Design: A comprehensive search strategy was undertaken across MEDLINE (PubMed), CINAHL, Embase, and Cochrane CENTRAL. Methods: Quality of life questionnaires utilized in studies investigating pediatric patients undergoing tonsillectomy for chronic tonsillitis or sleep‐disordered breathing were included. Methodological quality and data extraction were conducted as per Joanna Briggs Institute methodology. Results: Ten questionnaires were identified, consisting of six generic and four disease‐specific instruments. The Pediatric Quality of Life Inventory was the most commonly utilized generic questionnaire. The Obstructive Sleep Apnea‐18 was the most commonly utilized disease‐specific questionnaire. Conclusions: This review identified a range of generic and disease‐specific quality of life questionnaires utilized in pediatric patients who have undergone tonsillectomy with or without adenoidectomy for sleep‐disordered breathing or chronic tonsillitis. Important aspects of each questionnaire have been summarized to aid researchers and clinicians in choosing the appropriate questionnaire when evaluating the quality of life effects of tonsillectomy. Level of Evidence: NA Laryngoscope, 127:2399–2406, 2017